Pemberian Imunisasi Dasar Lengkap Pada Bayi - Arianggara, Andi Wilda; Pratiwi, Febrianty Hany; Tarigan, Renny Adelia (Jurnal Kesehatan Holistic, 2023)
Introduction: Basic immunization is one of the programs from the government given to babies and toddlers that has benefitsto protect health and increase endurance. Objective: This study aims to obtain more information about maternal behavior regarding the provision of primary immunization in the working area of the Tompobulu Health Center, Gowa Regency. Methods: This research uses qualitative methods (based on natural conditions) with a phenomenological approach (based on life experience). The core informants in this study were mothers who had babies 9-12 months and incomplete immunizations of 7 people and also key informants, namely immunization law experts and community leaders. Data collection was carried out by deepening the interview using interview guidelines. Result: The results showed that mothers' knowledge was still lacking about basic immunization, mothers had a negative attitude towards basic immunization, as well as mothers' poor actions/practices towards basic immunization. Conclusion: Improving education and promotion related to immunization is important for mothers who have toddlers.